Aperfeiçoamento e monitoramento de estação para tratamento e uso agrícola de água cinza no semiárido brasileiro - Silva, Adler Lincoln Severiano da (Universidade Federal Rural do Semi-Árido, 2018)
The water scarcity associated with environmental problems are factors that stimulate the development of technologies that allow the reuse of water in a sustainable way for agricultural and forestry purposes. In this sense, the research aimed to improve and monitor the performance of a gray water treatment plant and agricultural use installed at the Federal Rural Semi-Arid University in Mossoró-RN, Brazil. The station consists of equalization tank, septic tank, anaerobic filter, artificial ultraviolet reactor and infiltration ditch. In the ultraviolet reactor the height of the gray water slide, the distance between the lamps, the distance between the lamps and the liquid surface and the number of germicidal lamps were adjusted. The experiment was set up in a completely randomized design with four replicates in time, taking as collection points: gray water collected in the equalization tank (crude sample) and gray water collected in the artificial ultraviolet reactor (treated sample). treatments. The gray water sampling was performed on average every 32 days from July to October 2018, including determination of pH, temperature, electrical conductivity, turbidity, Chemical Oxygen Demand (COD), Biochemical Oxygen Demand ( BOD5,20), total suspended solids, total solids, sodium, potassium, calcium, magnesium, chloride, carbonate, bicarbonate, phosphorus, copper, zinc, iron, manganese, cadmium, nickel, lead, chromium, total coliforms and E. coli . Data were submitted to descriptive statistical analysis with mean and standard deviation. It was observed that the increase in the number of lamps from two to four lamps in the artificial ultraviolet reactor influenced greatly the decay of the population level of E. coli, and thus met the agricultural reuse standard of COEMA Resolution 02/2017 of the State of Ceará. The treatment system showed removals above 95% for turbidity, total suspended solids, COD, BOD and removals of 2.86 and 4.09 logarithmic units in relation to the total coliform and E. coli populations, respectively. Based on the international literature, the levels of heavy metals found in gray water do not compromise the production and development of agricultural crops
Keywords: Reúso; Efluente doméstico; Radiação ultravioleta; Ajuste tecnológico; Reuse; Domestic effluent; Ultraviolet radiation; Technological adjustment; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO